"x^2y''-2xy'+2(1+x^2)y=0, x>0\\\\"
Divide through by "x^2"
"y''-\\frac{2}{x}y'+\\frac{2(1+x^2)}{x^2}y=0\\\\"
For the equation of the form "y''+f(x)y'+g(x)y=F(x)." The substitution "y=v.e^{- \\int \\frac{f(x)}{2}dx}" is used.
So,
"y=v.e^{- \\int \\frac{-2}{2x}dx}\\\\\ny=v.e^{\\int\\frac{1}{x}dx}\\\\\ny=v.e^{\\ln x}\\\\\ny=vx\\\\\ny'=v+xv'\\\\\ny''=2v'+xv''"
Rewrite the equation
"(2v'+xv'')-\\frac{2}{x}(v+xv')+\\frac{2(1+x^2)}{x^2}vx=0\\\\\nxv''+2v'-\\frac{2v}{x}-2v'+\\frac{2(1+x^2)}{x}v=0\\\\\nxv''-\\frac{2}{x}v+\\frac{2(1+x^2)}{x}v=0\\\\\nxv''+\\frac{2}{x}v(-1+1+x^2)=0\\\\\nxv''+\\frac{2}{x}v(x^2)=0\\\\\nxv''+2xv=0"
divide through by "x"
"v''+2v=0" .
The associated auxilliary equation to this is ;
"m^2+2m=0\\\\\nm(m+2)=0\\\\\nm=0,m=-2"
So,
"v=A_1e^{0.x}+A_2e^{-2.x}\\\\\nv=A_1+A_2e^{-2x}"
But "v=\\frac{y}{x}"
"\\frac{y}{x}=A_1+A_2e^{-2x}\\\\\ny=x(A_1+A_2e^{-2x}) ,x>0"
Comments
Leave a comment